Kemampuan Pemahaman Matematis pada Materi Sistem Persamaan Linear Dua Variabel (SPLDV) Kelas VIII SMP Negeri di Kabupaten Sumba Timur - Nggaba, Mayun E; Nicolas, Nino; L. Ndakularak, Iona; I. Wadu, Darius (JURNAL MathEdu (Mathematic Education Journal), 2023)
To investigate students' mathematical comprehension abilities, a research was conducted in the form of a written test on 25 class VIII students at one of the Public Middle Schools in East Sumba Regency. These findings are supported by interviews and questionnaires. The ability to understand mathematics is the ability of students to interpret a concept and plan steps to solve the problems encountered. The results of the study using the Astuti indicator in the SPLDV material show that in the indicators: 1) being able to restate concepts, students get a score of 100 in the high category; (2) being able to classify objects based on whether or not the requirements that form the concept are met, students get a score of 100 in the high category; (3) being able to associate various mathematical concepts, students get a score of 58 in the moderate category; and (4) being able to apply concepts in various forms of mathematical representation, students get a score of 8 in the low category. In general, the ability to understand mathematics in solving SPLDV word problems is in the medium category, that is, not all students fulfill the third and fourth indicators.